Imaging in Propeller Flap Surgery - Ono, Shimpei (Semin Plast Surg, 2020)
Since propeller flaps are elevated as island flaps and most often nourished by a single perforator nearby the defect, it is challenging to change the flap design intraoperatively when a reliable perforator cannot be found where expected to exist. Thus, accurate preoperative mapping of perforators is essential in the safe planning of propeller flaps. Various methods have been reported so far: (1) handheld acoustic Doppler sonography (ADS), (2) color duplex sonography (CDS), (3) perforator computed tomographic angiography (P-CTA), and (4) magnetic resonance angiography (MRA). To facilitate the preoperative perforator assessment, P-CTA is currently considered as the gold standard imaging tool in revealing the three-dimensional anatomical details of perforators precisely. Nevertheless, ADS remains the most widely used tool due to its low cost, faster learning, and ease of use despite an undesirable number of false-positive results. CDS can provide hemodynamic characteristics of the perforator and is a valid and safer alternative particularly in patients in whom ionizing radiation and/or contrast exposure should be limited. Although MRA is less accurate in detecting smaller perforators of caliber less than 1.0 mm and the intramuscular course of perforators at the present time, MRA is expected to improve in the future due to the recent developments in technology, making it as accurate as P-CTA. Moreover, it provides the advantage of being radiation-free with fewer contrast reactions.